(untitled) - Tatham, Mark (New York, N.Y., 2006)
This book develops a framework for a fully explanatory theory of speech production integrating with speech perception. Emphasis is placed on the difference between static models (primarily descriptive) and dynamic models that attempt to show how the basic linguistics and phonetics are related in an actual human speaker/listener.
Keywords: Speech,Phonetics,Speech perception